Crystal structure and powder X-ray diffraction data for new Tb3CuAl3Ge2 compound. Issue 1 (20th February 2015) - Zeng, Chao; Lin, Guoqiang; Zeng, Weijing; He, Wei
Abstract : The crystal structure of new Tb3 CuAl3 Ge2 quaternary compound was studied by the Rietveld method from powder X-ray diffraction (XRD) data. The Tb3 CuAl3 Ge2 compound crystallized in the hexagonal Y3 NiAl3 Ge2 -type structure with space group P -62 m (no. 189) and lattice parameters a = 7.0041(2) Å, c = 4.1775(1) Å, V = 177.48 Å 3 . There is only one formula in each unit cell, Z = 1, and the density of Tb3 CuAl3 Ge2 is ρ x = 7.1696 g cm −3 . The reliability factors characterizing the Rietveld refinement results are R p = 6.43%, R wp = 8.65%, R B = 4.81%, and R F = 4.09%, respectively. The powder XRD data of Tb3 CuAl3 Ge2 were presented and the reliability of indexation is F 30 = 120.9(0.0073, 34).